NIMG-20. DIFFERENTIATION OF TREATMENT-RELATED CHANGES FROM TUMOR PROGRESSION FOLLOWING BRACHYTHERAPY IN PATIENTS WITH WHO II AND III GLIOMAS USING FET PET. (12th November 2021) - Bauer, Elena; Werner, Jan; Brunn, Anna; Deckert, Martina; Ruess, Daniel; Ruge, Maximilian; Celik, Eren; Fink, Gereon; Langen, Karl-Josef; Galldiks, Norbert
Abstract: BACKGROUND: Following brachytherapy, the differentiation of radiation-induced changes (e.g., radiation necrosis) from actual tumor progression using MRI is challenging. To overcome this diagnostic uncertainty, we evaluated the diagnostic value of O-(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET) PET in glioma patients treated with brachytherapy. MATERIAL AND METHODS: From 2006-2019, we retrospectively identified WHO grade II or III glioma patients (i) treated with brachytherapy using Iodine-125 seeds, (ii) equivocal or progressive MRI findings inside the radiation field, and (iii) additional FET PET imaging for diagnostic evaluation. Static FET PET parameters such as maximum and mean tumor-to-brain ratios (TBR) and dynamic FET PET parameters (i.e., time-to-peak, slope) were obtained. Diagnostic performances were calculated using receiver operating characteristic curve analyses and Fisher's exact test. Diagnoses were confirmed histologically or clinicoradiologically. RESULTS: Following brachytherapy, suspect MRI findings occurred after a median time of 33 months (range, 5-111 months). In 10 of 21 patients (WHO grade II, n=5; WHO grade III, n=16), treatment-related changes were diagnosed. The best diagnostic performance for identification of treatment-related changes was obtained using maximum TBRs (threshold < 3.20;accuracy, 86%; sensitivity, 100%; specificity, 73%; P=0.007). Mean TBRs reached an accuracy of 76% (threshold < 2.05; sensitivity, 89%; specificity, 64%; P=0.010). Dynamic PET parameters did not reach statistically significant results. CONCLUSION: Our data suggest that static FET PET parameters add valuable diagnostic information to diagnose radiation-induced changes in glioma patients treated with brachytherapy.